A Novel Wheat C-bZIP Gene, TabZIP14-B, Participates in Salt and Freezing Tolerance in Transgenic Plants - Zhang, Lina; Zhang, Lichao; Xia, Chuan; Gao, Lifeng; Hao, Chenyang; Zhao, Guangyao; Jia, Jizeng; Kong, Xiuying (Frontiers in Plant Science, 2017)
The group C-bZIP transcription factors (TFs) are involved in diverse biological processes, such as the regulation of seed storage protein (SSP) production and the responses to pathogen challenge and abiotic stress. However, our knowledge of the abiotic functions of group C-bZIP genes in wheat remains limited. Here, we present the function of a novel TabZIP14-B gene in wheat. This gene belongs to the group C-bZIP TFs and contains 6 exons and 5 introns; three haplotypes were identified among accessions of tetraploid and hexaploid wheat. A subcellular localization analysis indicated that TabZIP14-B was targeted to the nucleus of tobacco epidermal cells. A transactivation assay demonstrated that TabZIP14-B showed transcriptional activation ability and was capable of binding the abscisic acid (ABA) responsive element (ABRE) in yeast. RT-qPCR revealed that TabZIP14-B was expressed in the roots, stems, leaves and young spikes and was up-regulated by exogenous ABA, salt, low-temperature and polyethylene glycol (PEG) stress treatments. Furthermore, Arabidopsis plants overexpressing TabZIP14-B exhibited enhanced tolerance to salt, freezing stresses and ABA sensitivity. Overexpression of TabZIP14-B resulted in increased expression of the AtRD29A, AtCOR47, AtRD20, AtGSTF6 and AtRAB18 genes and changes in several physiological characteristics. These results suggest that TabZIP14-B could function as a positive regulator in mediating the abiotic stress response.